Anti-oomycete Activity of Chlorhexidine Gluconate: Molecular Docking and in vitro Studies - Thakuria, Dimpal; Khangembam, Victoria C.; Pant, Vinita; Bhat, Raja Aadil Hussain; Tandel, Ritesh Shantilal; C., Siva; Pande, Amit; Pandey, Pramod Kumar (Frontiers in Veterinary Science, 2022)
Saprolegniosis is one of the most catastrophic oomycete diseases of freshwater fish caused by the members of the genus Saprolegnia. The disease is responsible for huge economic losses in the aquaculture industry worldwide. Until 2002, Saprolegnia infections were effectively controlled by using malachite green. However, the drug has been banned for use in aquaculture due to its harmful effect. Therefore, it has become important to find an alternate and safe anti-oomycete agent that is effective against Saprolegnia. In this study, we investigated the anti-oomycete activity of chlorhexidine gluconate (CHG) against Saprolegnia. Before in vitro evaluation, molecular docking was carried out to explore the binding of CHG with vital proteins of Saprolegnia, such as S. parasitica host-targeting protein 1 (SpHtp1), plasma membrane ATPase, and TKL protein kinase. In silico studies revealed that CHG binds with these proteins via hydrogen bonds and hydrophobic interactions. In an in vitro study, the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of CHG against S. parasitica were found to be 50 mg/L. Further, it was tested against S. australis, another species of Saprolegnia, and the MIC and MFC were found to be 100 and 200 mg/L, respectively. At 500 mg/L of CHG, there was complete inhibition of the radial growth of Saprolegnia hyphae. In propidium iodide (PI) uptake assay, CHG treated hyphae had bright red fluorescence of PI indicating the disruption of the cell membrane. The results of the present study indicated that CHG could effectively inhibit Saprolegnia and hence can be used for controlling Saprolegniasis in cultured fish.